Abdominal aortic calcification, cardiac troponin I and atherosclerotic vascular disease mortality in older women. Issue 16 (24th December 2021) - Teh, Ryan; Prince, Richard L; Sim, Marc; Schousboe, John T; Raymond, Warren D; Szulc, Pawel; Lim, Wai; Hodgson, Jonathan M; Zhu, Kun; Kiel, Douglas P; Schultz, Carl; Thompson, Peter L; et al.
Abstract : Objective: Examine if two inexpensive measures of atherosclerotic vascular diseases (ASVD), abdominal aortic calcification (AAC) and high-sensitivity cardiac troponin I (hs-cTnI) provide complementary information for 10-year ASVD mortality and all-cause mortality risk in older women. Methods: 908 community-dwelling women without prevalent ASVD (≥75 years) were followed-up between 2003 and 2013. AAC and plasma hs-cTnI measures were obtained in 2003. AAC was assessed on lateral spine images using a semiquantitative method (AAC24). Linked health records were used for mortality outcomes. Results: Mean±SD age was 79.9±2.6 years. 276 (30.4%) women died during follow-up, including 138 (15.2%) ASVD-related deaths. AAC24 and hs-cTnI were independently associated with ASVD and all-cause mortality (p<0.001). The cohort was dichotomised into four groups: (1) low AAC24 (AAC24: 0 or 1) and <median hs-cTnI (n=163, referent), (2) moderate-extensive AAC24 (AAC24:>1) and <median hs-cTnI (n=280), (3) low AAC24 and ≥median hs-cTnI (n=148) and (4) moderate-extensive AAC24 and ≥median hs-cTnI (n=317). Compared with the referent group, a stepwise increase in relative hazard (HR (95% CI)) for ASVD mortality was seen at 2.39 (1.05 to 5.46), 3.18 (1.35 to 7.79) and 5.38 (2.44 to 11.85), respectively. A similar associations were observed for all-cause mortality, at 1.58 (0.99–2.52), 2.38 (1.46–3.89) and 3.02 (1.93–4.72), respectively (all p<0.05). Conclusion: Higher AAC and elevated hs-cTnI were associated with higher risk of ASVD mortality and all-cause mortality, independent of each other. Stratifying by moderate to extensive AAC and elevated hs-cTnI identified women at very high risk. Further studies investigating whether combining factors may improve risk prediction are needed. Trial registration number: ACTRN12617000640303.